Comparative analysis of world image peculiarities in Russian students and military personnel - B.S. Alishev; R.I. Atagunov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The image of the world is a holistic vision of reality, which is formed in the consciousness. It consists of a variety of individual ideas, all containing a certain evaluative component. Therefore, they take the form of mental images and beliefs. This paper analyzes only some of the beliefs of young men in two different fields of activity: students and military personnel (the latter is further subdivided into recruits and contract servicemen). In all groups, the belief in the danger/security of the world, its justice/injustice, the level of optimism, the level of life satisfaction, and the level of expression of some other social beliefs have been studied. It has been revealed that contract soldiers have the most specific image of the world, which is characterized by their belief in a fair world order, positive image of the self, the belief in their ability to control what is happening, and the belief in luck. These social beliefs are combined with a high level of optimism and life satisfaction. At the same time, it is the contract soldiers who perceive the world as a less dangerous “place” than the representatives of the other two groups.